Delivery room skin-to-skin contact in preterm infants affects long-term expression of stress response genes. (December 2020) - Hucklenbruch-Rother, Eva; Vohlen, Christina; Mehdiani, Nava; Keller, Titus; Roth, Bernhard; Kribs, Angela; Mehler, Katrin
Highlights: Delivery room skin-to-skin contact in preterm infants results in significantly altered stress response gene expression. Gene expression of CRH R2 correlates with HPA axis reactivity and mother child interaction at six months of age. Delivery room skin-to-skin contact might affect long-term stress response via regulation of gene expression. Delivery room skin-to-skin contact might contribute to improved outcome of prematurity. Abstract: Premature birth is a traumatic event that puts mother and child at risk for subsequent psychopathology. Skin-to-skin contact in the form of intermittent kangaroo mother care has been shown to positively affect the infant's stress response and cognitive development, but underlying mechanisms remain unclear. Moreover, first skin-to-skin contact is usually delayed for days after birth. In the delivery room skin-to-skin study (DR-SSC), a prospective randomized controlled trial conducted from 2/2012 to 7/2015, we set out to assess the effect of delivery room skin-to-skin contact on the infant's mRNA expression of six key molecules involved in stress response and neurobehavioral development at hospital discharge. 88 firstborn, singleton preterm infants (born at 25–32 weeks of gestational age) were included. In the delivery room after initial stabilization, infants were randomized to either 60 min of skin-to-skin or 5 min of visual contact with their mother. In this explorative add-on study on the original DR-SSC study, we determined the expression of six important stress response genes ( CRHR1 and CRHR2, AVP, NR3C1, HTR2A, and SLC6A4) in peripheral white blood cells of infants during routine blood sampling upon hospital discharge (corrected gestational age of 40 weeks). Infants were followed up to six months corrected age. Relative mRNA expression of the corticotropin releasing hormone receptor 2 ( CRH R2 ), the glucocorticoid receptor gene ( NR3C1 ), and the serotonin transporter gene ( SLC6A4 ) was significantly reduced in the delivery room SSC infants. Additionally, gene expression of CRH R2 showed a correlation with HPA axis reactivity and parameters of mother-child interaction at six months corrected age. Our results highlight the importance of delivery room mother-child skin-to-skin contact and underline the urgent need for in-depth studies on the underlying molecular mechanisms.